Efektivitas Whistleblowing Dalam Fraud Detection: Pilar Transparansi Atau Risiko Retaliasi? - Widyadhana, Kun Aulia; Kirana DP, Rina Tjandra (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Organizational fraud represents a significant global challenge, with estimated annual losses of 5% of revenue, totaling approximately US$4.7 trillion worldwide. This systematic literature review examines whistleblowing effectiveness as a fraud detection mechanism, analyzing the tension between its role as a transparency pillar and the retaliatory risks faced by whistleblowers. The study employed a qualitative Systematic Literature Review methodology, analyzing 25 peer-reviewed articles published between 2020-2025 from SINTA, Scopus, and registered E-ISSN journals. Literature was selected using keywords related to whistleblowing effectiveness, fraud detection, transparency mechanisms, and retaliation risk. Results demonstrate that whistleblowing systems significantly enhance fraud detection and prevention across both public and private sectors, with 24 of 25 reviewed studies confirming positive impacts. Effectiveness is influenced by individual attitudes, perceived behavioral control, organizational commitment, professional commitment, moral reasoning, and organizational culture. The integration of whistleblowing with forensic and investigative audit mechanisms creates a mutually reinforcing fraud detection framework. However, retaliation risk remains a substantial challenge, potentially undermining whistleblowing effectiveness. The study concludes that organizations must develop comprehensive whistleblower protection frameworks, cultivate supportive organizational cultures, ensure transparent report handling processes, and leverage technology to guarantee anonymity. A balanced approach between promoting transparency through whistleblowing and protecting whistleblowers from retaliation is essential for maximizing fraud detection effectiveness. Organizations are advised to integrate whistleblowing into comprehensive anti-fraud strategies with adequate protection mechanisms and whistleblower incentives.